The effect of exogenous growth regulators on salinity tolerance in Erucastrum strigosum - Gxaba, Nomagugu (University of the Western Cape, 2021)
Magister Scientiae (Biodiversity and Conservation Biology) - MSc (Biodiv and Cons Biol) === Randomized block experiments were conducted to examine the putative amelioratory effects of kinetin or gibberellic acid at concentrations (0, 4, 12.5, 40, and 125 μM) in Erucastrum strigosum plants subjected to a salinity series (0, 100, 200, 300, and 400 mM NaCl) in the greenhouse. When the highest salinity concentration (increased stepwise) was reached, growth effects in relation to water and cation content of the plants were evaluated. Growth and water content were reduced progressively with salinity treatments. Na+ concentration accumulated with salinity treatments to levels that were much higher than that of other cations (K+, Ca2+ and Mg2+) in both organs. However, it is noteworthy that Na+ distribution was more in shoots than in roots. In kinetin treated plants, shoot growth decreased whilst root growth increased with moderate hormonal treatments.